Relationships of new world Phlebotomine sand flies (Diptera: Psychodidae) based on fossil evidence - José Dilermando Andrade Filho; Reginaldo Peçanha Brazil (Memorias do Instituto Oswaldo Cruz, 2003)
The fossil record and systematics of phlebotomid sand flies, vectors of leishmaniasis and arbovirus in several regions of the world, strongly support that living genera existed long before the Oligocene (38 million years, myr). A common Phlebotominae ancestor was present in the Triassic period before the separations of continents (248 myr).